Integrating Half Rates of Dicamba and Atrazine with Increasing Sorghum Density and Nitrogen Rate for Palmer Amaranth Control - I. B. Cuvaca; A. J. Foster; R. Currie (Kansas Agricultural Experiment Station Research Reports, 2018)
Sorghum is an important crop in Kansas. However, in-season weed control options for sorghum are limited. This limitation is exacerbated by Palmer amaranth season-long interference and resistance to multiple herbicide modes of action. This 2-year study investigated the ability of a contrasting combination of cultural and chemical practices to control Palmer amaranth while maintaining or improving sorghum grain yield. Particular research emphasis was to evaluate the effect(s) of integrating half rates of dicamba and atrazine applied as PRE with increasing sorghum density and nitrogen rate on Palmer amaranth control and grain yield in an irrigated environment.
Keywords: Dicamba; Atrazine; sorghum; Palmer amaranth; nitrogen rates